Indian Influences on Balinese Culture : The Role of Hinduism and Buddhism in Present Day Bali - Ardhana, I Ketut; Wijaya, I Nyoman (International Research Journal of Management, IT & Social Sciences, 2017)
Indian culture has dominantly influenced the Indonesian people, particularly in the western part of the archipelago. This, which started centuries ago, can still be seen in the peoplesâ daily lives in social, cultural, economic and political matters. Both the Hindu and Buddhist lessons have been practiced in Bali, although it is argued that the Buddhist lessons had been developed earlier than the Hindu ones. These developments have strongly characterized Balinese daily life, so, it is very important to understand how the people anticipate and solve some crucial issues regarding the processes of modernization and globalization. There are some important questions that need to be addressed on the Indian influences in strengthening the Balinese culture from the earlier periods until the modern and even postmodern times. In this case, the specific questions are: Firstly, how did the Balinese accept these two lessons in their daily lives in the context of Balinization processes? Secondly, what kinds of tangible and intangible cultures of the Hindu and Buddhist lessons can be seen in the present day Bali? Thirdly, how do they strengthen the Bali identity or Balinization,Â  known as âAjeg Baliâ? Through this analysis, it is expected to have a better understanding of the issues of social, cultural, economic and political changes in Indonesia in general and Bali in particular in modern and postmodern times.